2023
DOI: 10.3390/molecules28227531
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Phytochemical Profiles, Cytotoxicity, Antiviral Activity, Antioxidant Potential, and Enzyme Inhibition of Vepris boiviniana Extracts

Kassim Bakar,
Nilofar,
Andilyat Mohamed
et al.

Abstract: In the present study, we performed comprehensive LC-MS chemical profiling and biological tests of Vepris boiviniana leaves and stem bark extracts of different polarities. In total, 60 bioactive compounds were tentatively identified in all extracts. The 80% ethanolic stem bark extract exhibited the highest activity in the ABTS assay, equal to 551.82 mg TE/g. The infusion extract of stem bark consistently demonstrated elevated antioxidant activity in all assays, with values ranging from 137.39 mg TE/g to 218.46 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…Spectroscopic (λmax = 220, 280, 305 nm) and spectrometric data (LC-MS/MS data) acquired in this study were in accordance with data published by Sun et al [49] and Bournine et al [44] for glaucine, therefore, the compound was unambiguously identified as glaucine, while compound 33 as its structural isomer, for example, takatonin (Pub-Chem). Seven compounds (16,22,23,26,27,31,32) detected in all samples, shared similar behavior to glaucine fragmentation and formed characteristics for aporphinoids, product ions with m/z greater than 200 Da [50]. The precursor ion [M+H] + of compound 23 at m/z 342.1715 was in accordance with the empirical molecular formula of C20H23NO4.…”
Section: Chemical Profile Of Extractssupporting
confidence: 53%
See 1 more Smart Citation
“…Spectroscopic (λmax = 220, 280, 305 nm) and spectrometric data (LC-MS/MS data) acquired in this study were in accordance with data published by Sun et al [49] and Bournine et al [44] for glaucine, therefore, the compound was unambiguously identified as glaucine, while compound 33 as its structural isomer, for example, takatonin (Pub-Chem). Seven compounds (16,22,23,26,27,31,32) detected in all samples, shared similar behavior to glaucine fragmentation and formed characteristics for aporphinoids, product ions with m/z greater than 200 Da [50]. The precursor ion [M+H] + of compound 23 at m/z 342.1715 was in accordance with the empirical molecular formula of C20H23NO4.…”
Section: Chemical Profile Of Extractssupporting
confidence: 53%
“…Positive and negative ions generated in ESI ion source (nebulizer pressure: 35 psig, drying gas temp: 275 °C, drying gas flow: 10 L/min) were fragmented at the collision energies of 10 and 30 eV and detected in a range of 50–1700 m / z . Other working parameters were as follows: sheath gas temp: 325 °C, sheath gas flow: 12 L/min; skimmer 65 V, capillary V (+): 4000 V, and fragmentor 140 V. The identification was based on accurate masses and fragmentation patterns, also supported by available literature sources [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Oxidative stress refers to the disparity between the defensive capabilities of the antioxidant system and the generation of reactive oxygen species. Plant antioxidants are commonly acknowledged as nutraceuticals, serving to eliminate free radicals and functioning as antioxidants [ 34 , 35 ]. Compounds with reductive properties have traditionally been employed in the food industry to protect products from oxidation [ 36 ].…”
Section: Resultsmentioning
confidence: 99%